Performance Analysis of Radio Resource Allocation to Maximize Power Efficiency in Device-To-Device Communication - Shilvy Fatma Fitria Rachmawati; Vinsensius Sigit Widhi Prabowo; Lista Anggayani; Nachwan Mufti Adriansyah (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2023)
Technological developments in the field of telecommunications have progressed. However, the more cellular network users, the more traffic on the Base Station (BS) will be. One way to overcome this is to implement a Device-To-device (D2D) communication system. However, when D2D User Equipment (DUE) reuses Cellular User channel resources Equipment (CUE), then interference will occur. This research is conducted to address interference problems and maximize energy efficiency for CUEs and DUEs by implementing the Greedy algorithm with additional power control. The aim is to block unnecessary resources and optimize resource allocation. The Optimal Power Control (OPC) scheme will utilize the transmit power threshold. The simulation scheme for the D2D communication system used is the uplink and underlay mode single-cell system model. Where the DUE pair will use the same resources as the CUE that has been given by the BS. Resources in CUE can only be reused by one pair of DUEs, and vice versa. The greedy algorithm using power control gets superior performance at a sum rate of 1.79 × 107 bps with an increase of 36.03%. Spectral efficiency of 2.49 bps/Hz with an increase of 36.03%. The power efficiency of 2.08 × 103 bps/mw with an increase of 118.47%. Based on the result the greedy algorithm without power control gets superior performance at CU Fairness of 1 with an increase of 50.14%.